Nuclear power in the Middle East: Financing and geopolitics in the state nuclear power programs of Turkey, Egypt, Jordan and the United Arab Emirates. (April 2021) - Hickey, Samuel M.; Malkawi, Salaheddin; Khalil, Ayman
Highlights: Narrative behind nuclear program development for four Middle Eastern states is presented. Financial and ownership models employed and the different points of leverage in negotiations. Commercial obstacles mainly determine the role of the state in energy policy making. Innovative financing models are needed to mitigate risks of construction delay. Abstract: The International Atomic Energy Agency proscribes contracting and ownership models for the construction and operation of new nuclear power plants, but a country-specific risk allocation strategy must contend with long-term interdependencies codified with nuclear leaders. Four case studies examine the State's role in nuclear negotiations and illustrate an exchange of sovereign assurances for better financing to overcome the commercial obstacles to construction. Turkey is employing the Build-Own-Operate model for the first time ever in nuclear. Egypt's state-owned industry model retains all the risk, and sovereign assurances are exchanged for favorable financial terms. Jordan and the United Arab Emirates (UAE) occupy the middle ground by attempting joint-ownership models, but their energy demand and need for foreign financing is vastly different. In the complex security environment of the Middle East, sovereign assurances or the exposure of state assets may be left as a last resource to irreconcilable political realities, which means the negotiations must be analyzed in its historical context. There is a need for cooperation on a regional level to enhance the negotiating powers of nuclear newcomers. Commercially viable financing for nuclear construction can be awarded, but the State must identify the sovereign assurances it is willing to grant.